The Association between breast cancer and some lifestyle factors among women in Sulaymaniyah city, Iraq: Case-Control study - Shali, Alla Abdulqader; Mohammed, Atiya K. (Sulaimani Journal for Pure and Applied Sciences, 2020)
A healthy lifestyle could contribute to decreasing breast cancer in women at high risk. This study was performed to find out the association between some lifestyle factors, and breast cancer among women in Sulaymaniyah city. A retrospective case-control study was carried out, from July 2019 to October 2019. Purposive sample 400 women attending Hiwa Hospital and Teaching Hospital were assigned to either the case or group. A questionnaire was constructed by the researcher to elicit detailed information related to study objectives. All subjects were completed as in-person interview techniques. The questionnaire is presented to a panel of 12 experts to check the validity. Internal consistency and reliability were measured by using Cronbach's alpha formula on the questionnaire list. Analyzing and interpreting data using the application of descriptive statistical analysis, inferential chi-square test. The results have revealed that there was a significant association between breast cancer and educational level, residence area, body mass index, abortion, hormonal contraception, long-duration contraception use above 6 years, benign breast disease. The study concludes that women with higher Body mass index riskier to breast cancer in their lives.
Keywords: Breast cancer; lifestyle factors; Sulaymaniyah City; Control study